Capital budgeting practices of Malaysian companies - Chong, Xiao En (2018)
This study presents the capital budgeting practices of Malaysian companies through 4 stages: Identification, Development, Selection and Control. It is based on a questionnaire sent to 240 Malaysian companies of various industries and sizes, which received a response rate of 15%. The main purpose of the study is to examine the capital budgeting practices of Malaysian companies and to identify possible gaps between theory and practice. The study shows that Malaysian companies have a structured investment appraisal process to support long term objectives and are progressively moving towards sophisticated capital budgeting practices such as the use of Discounted Cash Flow method, probabilistic type of risk assessment tools, and Real Options. However, a theory-practice gap remains. Payback method is still the most frequent tool used by Malaysian companies to evaluate potential investments. Among the Discounted Cash Flow method, Internal Rate of Return is preferred over the theoretical superior Net Present Value. The study also aims to investigate the determinants of sophisticated capital budgeting practices. In the context of this study, sophistication is assessed in totality with respect to capital budgeting process. Three sophistication indexes are constructed to regress on company characteristics using a robust ordered probit model. Results indicate that the type of industry that a company operates in and its management structure are related to the sophistication of capital budgeting practices. A significant higher level of sophistication is found for companies in the service industry and those that appoint non-owners executives to manage the company. Similar with other empirical research, this study has its limitations, such as the sampling method, sample size, and response bias. A wider set of data and determinants including top management characteristics could have perhaps enhance the findings of this study. Nevertheless, the findings of this study can be utilized to encourage better capital budgeting practices and to improve overall decision making of Malaysian companies.